Obtenção quimiosseletiva de trialometil-β-dicetonas via reações de acilação de acetais - Frigo, Leandro Marcon (2009)
This work presents an Acylation Method of Acetals applied to the quimioseletive obtention of trifluormethyl-β-diketones, incluing acetals derived from not symmetrical ketones and functionalized substituents. Five known knotrifluormethyl-β-diketones: 1-fenil-2-metil-4,4,4-trifluor-1,3-butanodiona and 2-trifluoracetilciclododecanona, and unknown with formula F3CCOCH2COR where R = -CH2(2-MeO-C6H4), -(CH2)2Ph, CH(SMe)Me were obtoined In additions two new trichloromethyl-β-dicetonas, Cl3CCOCH2COR where R = -(CH2)2Ph, CH(SMe)Me were obtoined . The synthesis of the dimethoxy acetals (1a-g) was lead from already established way, supplying the products 1a-g in good incomes, >85% after distillation. The acetals were acetylated with trifluoroacetic anhydride and trichloacetyl chloride according to Acylation Method of Acetals that made possible the regiosespecific synthesis of the β-alkoxyvinyl trihalomethyl ketones 2a-g and 3d, e. The acylated products after that were hydrolyzed until the respective β-dicarbonyls composites 4a-e, 4h, i and 5d, e. All the products were identified and characterized from the data of NMR and spectrometry of masses. The analysis of the results of this work and from works related to trifluormethyl-β-diketones synthesis described on the literature made possible the comparison between the Acylation Method of Acetals with haletos and trialoacetic anhydrides and the Acylation Method of Enolates with trifluoracetate of alquila (called Claisen Method).